THE INFLUENCER AND HEDONIST LIFESTYLE OF DIGITAL SOCIETY - Rasdica Denara Hernowo Puteri (The Indonesian Islamic Studies and International Relations Association (Insiera), 2018)
Influencers become a booming fashion icon among the society. They represent themselves with an ideal identity to the society, from fashion, makeup, vacation spots and other modern lifestyles. Influencers want to make themselves as role model for society and become a culture followed by society. Influencers have power relations to their followers, so they can affect their followers to follow the culture brought by them. Previous research said that influencer became a phenomenon in the new media era towards the establishment of a hedonist lifestyle of digital society. Researcher argued that in addition to the power relation from the influencer to their followers, the emotional pleasure problem of the followers in consuming, especially in consuming the same stuff as the influencer, becomes an important aspect to the establishment of hedonist lifestyles. This research uses a qualitative approach with interviews and visual analysis from influencer's Instagram account.